Optimizing Decision Making through a Strategic Approach in Educational Institutions - Muamar Qadafi; Abdul Kodir Nurhasan (Gestion Educativa, 2025)
Decision making is one of the managerial functions that determines the direction and success of educational institutions in achieving their vision and mission. However, in practice, there are still many institutions that make decisions reactively, not based on data, and with minimal participation. This research aims to examine how strategic approaches are applied in the decision-making process in the educational environment and its impact on institutional performance. This study uses a qualitative approach with a case study design. Data was collected through in-depth interviews, observations, and documentation studies at one of the educational institutions that applied strategic management principles. The results show that vision-mission-based decision-making, supported by academic and non-academic data, and involving various stakeholders, contributes significantly to improving service quality, program effectiveness, and school community satisfaction. However, the implementation of this approach still faces obstacles, such as data limitations, time pressures, and external interventions. Transformative leadership is a key factor in driving more directed, collaborative, and sustainable decision-making patterns. These findings reinforce the importance of optimizing strategic decision-making in strengthening the managerial effectiveness and competitiveness of educational institutions amid the challenges of the VUCA era.